ANALISIS KUALITAS AIR IRIGASI BERDASARKAN PARAMETER FISIKOKIMIA DAN STRUKTUR FITOPLANKTON DI AREA SAWAH DI KECAMATAN NOEMUTI - Santiari, Made; Priyambodo, Hernur Yoga; Moi, Maria Yasinta (JURNAL BIOSENSE, 2026)
Rice production depends on the quality of irrigation water. Irrigation water in the rice fields of Noemuti District has never been tested, so this research was conducted. This research is a quantitative study. Water test sampling points for measuring physical, chemical, and phytoplankton parameters were 3. Parameters of pH, DO, temperature, and TDS were measured in the field, while the parameters of Nitrate (NO3-N) and Total Phosphorus (PO4-P) were tested in the laboratory. Phytoplankton collection began with 100 liter water sample filtered using a 20 μm plankton net, the results of the filtration were put into a 100 mL bottle, then given formalin, and then analyzed in the laboratory using a Sedgewic Rafter Counting Chamber (SRCC) and a microscope. The values ​​of physical and chemical parameters were compared with quality standards, and the quality status calculated using the pollution index method. The obtained plankton were identified by comparing with various literatures. The abundance, diversity index, dominance index and uniformity index of phytoplankton calculated. The values ​​of physical and chemical parameters at the three stations met the quality standards. The pollution index values ​​at the three stations were included in the category of meeting the quality standards. The diversity index values ​​at the three stations fall into the moderate community stability and moderate diversity categories (moderately polluted water quality). The moderately polluted water quality category based on the H' value differs from the water quality category that meets quality standards as seen from the pollution index value. The uniformity index is high, and the community dominance index is low at all three stations. Irrigation water based on physical and chemical parameters can be used for agricultural purposes, but based on the diversity index, it should be treated first.